1999
DOI: 10.1002/(sici)1099-114x(19990310)23:3<217::aid-er473>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spray characteristics on combustion performance of a liquid fuel spray in a gas turbine combustor

Abstract: Spray characteristics like mean drop diameter and spray cone angle play an important role in the process of combustion within a gas turbine combustor. In order to study their effects on wall and exit temperature distributions and combustion efficiency in the combustor, a numerical model of a typical diffusion controlled spray combustion in a can‐type gas turbine combustion chamber has been made. A simple k–ϵ model with wall function treatment for near‐wall region has been adopted for the solution of conservati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…we use the sequence ( ) in (17), which converges weakly to . We conclude that lies in the closure of P N , and thus that P N , [ , ] is a subset of the closure of P N , in P N .…”
Section: International Journal Of Stochastic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…we use the sequence ( ) in (17), which converges weakly to . We conclude that lies in the closure of P N , and thus that P N , [ , ] is a subset of the closure of P N , in P N .…”
Section: International Journal Of Stochastic Analysismentioning
confidence: 99%
“…The importance of predicting droplet size can be seen from the wide range of applications utilizing sprays [17,18]. Because of the importance of this problem, novel approaches for measuring size distribution of droplet size in sprays have been developed [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Results show a wide broadening of the droplet size distribution and SMD when compared to idle. Since most of the fuel is within the larger droplets, the evaporation rate decreases, causing a slower combustion reaction and a reduction in combustion efficiency (Datta and Som, 1999;Lefebvre;1985, Lefebvre, 1998. Beck et al (1989), as shown in Fig.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…An in-flight shutdown can occur due to an engine malfunction, external factors (such as volcanic ash) or a deliberate shutdown by the pilot. However, for each scenario, the chamber conditions (temperature, pressure and air velocity), chamber volume, and spray characteristics (Datta and Som, 1999;Lefebvre, 1985; Lefebvre, 1998) greatly determine the relight and pull-away capability of the engine. A useful unit of measurement in terms of spray quality is the Sauter Mean Diameter (SMD), defined as the droplet diameter which has the same volume to surface area ratio as that of the whole spray.…”
Section: Introductionmentioning
confidence: 99%
“…Datta and Som [16] also used the k À e turbulence model to examine the effect of spray cone angle and drop diameter on wall and exit temperature distributions and combustion efficiency in the combustor. The eddy break-up (EBU) combustion model was used to analyze the burning of n-hexane (C 6 H 14 ) fuel in their study.…”
mentioning
confidence: 99%